(untitled) (Dhaka University Journal of Biological Sciences, 2020)
This study was aimed at evaluating the association between gestational diabetes mellitus (GDM) and fetal birth weight considering duration of pregnancy, maternal age and body mass index (BMI). This was a retrospective cross-sectional study followed by cohort type of study. Initially, pregnant women in their 24 to 28th week of gestation were selected for determining their fasting blood glucose (FBG) level and blood glucose level 2 hrs after 75 g oral glucose intake. The cut-off value for the diagnosis of GDM was > 5.3 mmol/l for FBG level and > 8.6 mmol/l for taking 75 g oral glucose intake after 2 hrs. Both GDM and control group subjects were followed up to neonatal period to find out neonatal outcomes. Among the total 215 subjects, 84 pregnant women were selected with GDM and rest 131 were control. It is found that GDM alone had a significant (p = 0.05) positive effect on both the duration of pregnancy and fetal birth weight, but not on maternal BMI. Both the effects of duration of pregnancy and GDM are considered together on fetal birth weight, only GDM had significant impact on fetal birth weight compared to the control group. Similarly, when the effect of maternal BMI and GDM is considered together on fetal birth weight, only GDM group was found to have significant effect on fetal birth weight. Parallel results were observed for the effect of both maternal age and GDM on fetal birth weight. In binary logistic regression analysis, when the differences are considered in maternal age, duration of pregnancy and maternal BMI along with GDM, both maternal age ≥ 35 years (OR: 9.43, p = 0.001) and GDM (OR: 10.60, p = 0.003) was found to have significant positive effect on fetal birth weight. It was found that the GDM showed significant influence on fetal birth weight considering the effects of maternal age, duration of pregnancy and maternal BMI. Dhaka Univ. J. Biol. Sci. 29(2): 209-218, 2020 (July)